War, the Presidency, and Legislative Voting Behavior. Issue 1 (5th September 2012) - Howell, William G.; Rogowski, Jon C.
<x xml:space="preserve">Abstract</x> An extraordinary body of scholarship suggests that war, perhaps more than any other contributor, is responsible for the emergence of a distinctly modern presidency. Central to this argument is a belief that members of Congress predictably and reliably line up behind the president during times of war. Few scholars, however, have actually subjected this argument to quantitative investigation. This article does so. Estimating ideal points for members of Congress at the start and end of the most significant wars in the past century, we find consistent—albeit not uniform—evidence of a wartime effect. The outbreaks of both world wars and the post‐9/11 era—though not the Korean or Vietnam wars—coincided with discernible changes in member voting behavior that better reflected the ideological leanings of the presidents then in office. In the aftermath of all these wars, meanwhile, members shifted away from the sitting president's ideological orientation. These findings are not confined to any single subset of policies, are robust to a wide variety of modeling specifications, and run contrary to scholarship that emphasizes ideological consistency in members' voting behavior.